Expectation value based cluster expansion. Issue 9 (7th June 2013) - Leymann, Heinrich A. M.; Foerster, Alexander; Wiersig, Jan; Ulrich, Sven M.; Jetter, Michael; Michler, Peter
Abstract We outline a new formulation of the cluster expansion to derive equations of motion for open quantum systems. Our method uses expectation values instead of correlation functions. The algebraic effort to derive the equations is reduced and the approach is more intuitive. We demonstrate the efficiency of our method by applying it to the damped Jaynes‐Cummings model. This model is a good starting point to investigate quantum dot based laser systems. Further we will examine the convergence properties of the cluster expansion for various orders. (© 2012 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)